Comparação dos sistemas de alvenaria de vedação: bloco de concreto celular autoclavado x bloco cerâmico - Fabiana de Carvalho Ferraz (2011)
This work intends to compare the sealing masonry systems made with autoclaved aerated concrete block, AACB, with the ones made with ceramic blocks focusing on mechanical aspects. The simple compressive strength of blocks, prisms and walls has been evaluated by means of laboratory tests. In this study, two types of mortar have been evaluated: factory pre-blended mortar and site-dosed mortar with ratio 1:3:8 (cement: lime: sand). The determination of mechanical behavior has been made using the following tests: block compressive strength; prism compressive strength; wall compressive strength; mortar bending tensile strength; mortar axial compressive strength and hard body impact test. AAC blocks with dimensions of 12,5 cm x 30 cm x 60 cm (thickness x height x length), ceramic blocks with dimensions of 14 cm x 19 cm x 29cm (thickness x height x length), industrialized mortar and site-dosed mortar with ratio 1:3:8 (cement: lime: sand) have been used during the tests. AACB system has presented compressive strength higher than the ceramic block system. Using industrialized mortar has shown greaterefficiency and more uniform behavior. AACB system with using of industrialized mortar has presented the best performance among the studied systems regarding the analyzed aspects. AACB system has presented conformity with normative requests regarding the analyzedaspects. The ceramic block system has not presented conformity with normative requests regarding the analyzed aspects.